2013
DOI: 10.1016/j.bjid.2012.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of reactive Epstein–Barr Virus (EBV) in Iranian patient with different subtypes of multiple sclerosis (MS)

Abstract: These findings provide further support for the detrimental effects of Epstein-Barr virus in the reactivation of multiple sclerosis attacks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 40 publications
1
11
1
Order By: Relevance
“…However, in the Iranian population, previous studies have been conflicting-with one study showing higher seropositivity and antibody titres in MS patients as compared to controls [9] and another investigation reporting no difference [3]. In our study, we found all MS patients to be seropositive for EBV as compared to 82 % of healthy controls.…”
Section: Discussioncontrasting
confidence: 66%
“…However, in the Iranian population, previous studies have been conflicting-with one study showing higher seropositivity and antibody titres in MS patients as compared to controls [9] and another investigation reporting no difference [3]. In our study, we found all MS patients to be seropositive for EBV as compared to 82 % of healthy controls.…”
Section: Discussioncontrasting
confidence: 66%
“…Antibody levels against EBV were compared between 46 RRMS, 11 SPMS, and 21 PPMS patients in Iran [ 18 ]. All cases were prevalent, and disease duration at sample collection was not reported.…”
Section: Resultsmentioning
confidence: 99%
“…Immunofluorescence assay (IFA), enzyme immunosorbent assay (EIA) and ELISA are commonly used to detect EBV antibodies (Balfour et al, 2013;Binnicker et al, 2008;Ramroodi et al, 2013;Xiong et al, 2014). IFA and EIA use a microscope to judge results individually, with a certain subjectivity, which influences the specificity and sensitivity of the detection method (Debyser et al, 1997).…”
Section: Discussionmentioning
confidence: 99%